Perancangan Web Sistem Informasi Tes Kemampuan Bahasa Inggris Kelas Menggunakan Metode Fisher Yates Shuffle - Andri Wijaya; Frendy Dodo Chang (Komunitas Dosen Indonesia, 2023)
Information technology has been rapidly developing over the past few decades, and the COVID-19 pandemic has further accelerated the adoption and implementation of technology in various aspects of our lives, particularly in the business sector and education., where improvements in the learning system that were originally offline become online, practical, and easy. Currently, information regarding the English Test at Faculty of Social Sains and Humanities Buddhi Dharma University (UBD) is still running manually starting from registration, scheduling, exam, and announcement of English test results which of course requires more time for both participants and faculty staff. In order to boost students English knowledge, an English comprehension exam test is needed as organized by the faculty, that is English Proficiency Test (EPT). The design of this EPT information system, a part of being able to change the manual method, and also to simplified the EPT procedure. The new system is using website which combined with Fisher-Yates Shuffle method for randomization the exam test to reduce fraudulent actions in the process of conducting English training tests, being followed by 94 respondents as English training participants, system tested using the User Acceptance Test (UAT) method with five aspects of quality components. The results obtained that the system built had a good criteria with a value of 75.93%.